If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -15 = 6x Reorder the terms: -15 + 9x = 6x Solving -15 + 9x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -15 + 9x + -6x = 6x + -6x Combine like terms: 9x + -6x = 3x -15 + 3x = 6x + -6x Combine like terms: 6x + -6x = 0 -15 + 3x = 0 Add '15' to each side of the equation. -15 + 15 + 3x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = 0 + 15 3x = 0 + 15 Combine like terms: 0 + 15 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| X-3/4(2x-12)=7x/2+5 | | 7x-12-4x=5x-7 | | f(x)=3x+36 | | 27/8(29/6k+1/4)=-4149/32 | | 56x^2-23x=63 | | (7/w-4)=(-5/(2w-8))+4 | | 3x+y+x+y= | | (x-8)-(6x+4)= | | -20=-5+5y | | 100x-35= | | 5+1/8x=15 | | q-25=81 | | 9x-3y=81 | | 2(6y-4)-x=-4(y-3) | | u^2-u-42=0 | | 12x-4y=96 | | 2x-4=5x-24 | | 4(x-15)=16x | | 12=3w+6 | | 2(3y-6)=5(y+2) | | 4x-7=15x+4 | | X+4/2x=4 | | x/3=10+15 | | 5x-8x+3=x-2+5 | | 0.12y+0.02(y+5000)=600 | | 3y+12=9y-18 | | 4/6x+2=6 | | 9x+2=11x-2 | | 8(x+7)+8=8x+2 | | 1/4(x-12)+1/2(x+2)=x+4 | | 6x+2x=36+12 | | 9+8a+17/3=-2 |